Penerapan Media Pembelajaran untuk Meningkatkan Hasil Belajar Siswa Teknik Instalasi Tenaga Listrik - Noor Fazira; Doni Tri Putra Yanto (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2026)
This study aims to determine the differences in student learning outcomes between a class that used the Quizizz application as a learning medium and a class that applied conventional methods in the subject of Basic Electrical Engineering for Grade X TITL students at SMK Negeri 1 Bonjol. The research employed a quasi-experimental method with a pretest-posttest control group design. The subjects of the study were 56 Grade X TITL students in the 2025/2026 academic year, who were divided into experimental and control groups. The research instrument consisted of a learning achievement test administered in the form of both a pretest and a posttest. Data were analyzed using the t-test to examine the differences in learning outcomes between the two groups. The results indicated a significant difference between the learning outcomes of the experimental class and the control class. The average score of students in the experimental class was higher than that of the control class, demonstrating that the use of Quizizz is effective as an interactive learning medium to enhance motivation, engagement, and overall student learning outcomes in Basic Electrical Engineering.